PENGARUH MANAJEMEN PERKANTORAN TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KANTOR BAPPEDA PROVINSI KALIMANTAN TIMUR - Sri Hartati (ADMINISTRASI PUBLIK, 2018)
Sri Hartati, Effect of Office Management on Employee Effectiveness At Bappeda Office of East Kalimantan Province, under the guidance of Mrs. Salasiah, S. Sos., M.Si as mentor I and Mr. H. Ahmad Jubaidi, S. Sos, M. Si as Mentor II.The purpose of this study is to determine the Effect of Office Management on Employee Effectiveness at Bappeda Office of East Kalimantan ProvinceThe results showed that Office Management has a positive effect on the Effectiveness of Employees at the Bappeda Office of East Kalimantan Province. Based on the data in the interval table it can be seen that the value of rxy coefficient correlation on that calculation is 0.649 it is above> 0.202 thus there is closeness relationship between independent variables to the dependen variable is quite strong. The value of rxy coeffeicient correlation or r arithmetic is 0.649 while the r value of product moment  or r table at the level of significance alpa is 0,05 or 5% N = 98-1 is r0,05, 24 = 0,202 (contained in attachment). Therefore the value of r xy> r table (0.649 > 0.202) then the hypothesis proposed in this study is accepted that the variables of office management have a significant effect on the effectiveness of employees at the Bappeda Office of East Kalimantan Province.From the calculation results above can be seen that the value of correlation coefficient r = 0.649. Furthermore, the value in the interpretation table according to a conservative size. Based on the interpretation table the value (r) of 0.604 lies between 0.600 up to 0.800 that fall into the quite high category.From the calculation result obtained r arithmetic count 0,649 then compared with price critic at table r Product Moment at N = 98 with 95% significance level obtained critic value = 0,202. Thus proved: r arithmetic = 0.649> r table = 0.202 at σ = 95%Thus there is a positive and significant influence office management on employee effectiveness At Bappeda Office of East Kalimantan Province.